Digital Dividends: Redefining Banking Choices of Women in Bangladesh (Global Journal of Management and Business Research, 2024)
Different perceptions shape different banking choices. This study investigates women's perceptions of banking channels in Bangladesh. It also explores the diverse catalysts influencing banking choices and women's challenges in shaping their preferences. We used a qualitative interview method to understand female perceptions of banking channels. We did a thematic analysis of interviews with thirty female banking system users as the sample. Using the purposive sampling method, we selected the respondents for the interviews. To analyze the coded interviews, we employed an atlas. ti 2023, a qualitative data analysis software. The study found that quick and convenient access, efficient financial management, cost-effectiveness and high security play a significant role in shaping women's banking behaviours. The study also found that women encounter challenges related to digital literacy, security and complex banking systems. Moreover, the study found that the benefits of time-saving mechanisms are replaced by the burden of high transaction costs, challenging low-income thresholds. Therefore, the authors of this article recommend digital literacy initiatives, security enhancements, and cost mitigation strategies. The study emphasized the need for policy interventions to promote women's financial inclusion.
Keywords: sustainability; women; bangladesh; financial inclusion; digital banking